When mobile policies drive against the wall. Limits of policy transfer using the example of Business Improvement Districts in Germany - Michel, Boris (Berichte. Geographie und Landeskunde, 2013)
This paper argues that recent debates on policy transfer and mobile policies would benefit by challenging the implicit focus on " successful" cases and instead take failure more seriously - both on an empirical as well as conceptual level. Drawing on a research project on the globalization of Business Improvement Districts, it is argued that the history of Business Improvement Districts in Germany should not be read as a story of successful transfer, as has been done by critical as well as sympathetic scholars and advocates. Business Improvement Districts are far from becoming major agents of urban change - be it agents of neoliberal urbanism and private urban governance or be it agents of urban renewal and civil society. Focusing on successful cases and projects, it is argued, reifies the perspective of those agents that are able to articulate their voices within hegemonic discourses.